COVID-19 mortality in women and men in sub-Saharan Africa: a cross-sectional study - Claire Somerville; Isotta Triulzi; Giuseppe Turchetti; Benido Impouma; Olivia Keiser; Jyoti Dalal; Ananthu James; Benedict Nguimbis; Gabriela Guizzo Dri; Akarsh Venkatasubramanian; Lucie Noubi Tchoupopnou Royd; Sara Botero Mesa; et al. (BMJ Global Health)
Introduction Since sex-based biological and gender factors influence COVID-19 mortality, we wanted to investigate the difference in mortality rates between women and men in sub-Saharan Africa (SSA).Method We included 69 580 cases of COVID-19, stratified by sex (men: n=43 071; women: n=26 509) and age (0–39 years: n=41 682; 40–59 years: n=20 757; 60+ years: n=7141), from 20 member nations of the WHO African region until 1 September 2020. We computed the SSA-specific and country-specific case fatality rates (CFRs) and sex-specific CFR differences across various age groups, using a Bayesian approach.Results A total of 1656 deaths (2.4% of total cases reported) were reported, with men accounting for 70.5% of total deaths. In SSA, women had a lower CFR than men (mean CFRdiff = −0.9%; 95% credible intervals (CIs) −1.1% to −0.6%). The mean CFR estimates increased with age, with the sex-specific CFR differences being significant among those aged 40 years or more (40–59 age group: mean CFRdiff = −0.7%; 95% CI −1.1% to −0.2%; 60+ years age group: mean CFRdiff = −3.9%; 95% CI −5.3% to −2.4%). At the country level, 7 of the 20 SSA countries reported significantly lower CFRs among women than men overall. Moreover, corresponding to the age-specific datasets, significantly lower CFRs in women than men were observed in the 60+ years age group in seven countries and 40–59 years age group in one country.Conclusions Sex and age are important predictors of COVID-19 mortality globally. Countries should prioritise the collection and use of sex-disaggregated data so as to design public health interventions and ensure that policies promote a gender-sensitive public health response.